2007
DOI: 10.1021/ja067209i
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Reaction Pathways Followed upon Reduction of Oxy-Heme Oxygenase and Oxy-Myoglobin as Characterized by Mössbauer Spectroscopy

Abstract: Activation of O 2 by heme-containing monooxygenases generally commences with the common initial steps of reduction to the ferrous heme and binding of O 2 followed by a one-electron reduction of the O 2 -bound heme. Subsequent steps that generate reactive oxygen intermediates diverge and reflect the effects of protein control on the reaction pathway. In this study, Mössbauer and EPR spectroscopies were used to characterize the electronic states and reaction pathways of reactive oxygen intermediates generated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
60
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 60 publications
7
60
0
Order By: Relevance
“…This is typical for low-temperature oxyMb spectra [104]. It has been shown that the oxyMb is quite easily one-electron-reduced by 60 Co g-irradiation [67] [104], as well as oxyP450, oxyHRP, and oxyCPO [29] [105] [106]. Similar spectroscopic changes as observed by 60 Co g-irradiation are observed for synchrotron X-ray-irradiated Mb compound III (Fig.…”
supporting
confidence: 66%
See 2 more Smart Citations
“…This is typical for low-temperature oxyMb spectra [104]. It has been shown that the oxyMb is quite easily one-electron-reduced by 60 Co g-irradiation [67] [104], as well as oxyP450, oxyHRP, and oxyCPO [29] [105] [106]. Similar spectroscopic changes as observed by 60 Co g-irradiation are observed for synchrotron X-ray-irradiated Mb compound III (Fig.…”
supporting
confidence: 66%
“…An issue to be raised is if it is the peroxyMb or the hydroperoxyMb state that has been trapped and solved with X-ray diffraction. Optical absorption, EPR, and Mçssbauer spectroscopy have shown that the cryoradiolytically reduced oxyMb is a peroxyMb state, and that temperatures near 185 K are needed to induce a proton transfer resulting in hydroperoxyMb [28] [67]. The ca.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These fleeting intermediates of heme enzyme catalysis could not be isolated in ambient conditions, despite numerous attempts. However, being immersed in liquid nitrogen, they are stable for many months and can be studied using various spectroscopic methods, such as EPR (62,65,67,73-76), UV-Vis absorption spectroscopy (58,59,69,70,76-79), resonance Raman (69,71,72,79,80), Mössbauer (67), and EXAFS (81). …”
Section: Introductionmentioning
confidence: 99%
“…It can also be noted that the conclusion that the HOMO of heme group is formed by d orbitals of Fe atom rather than orbitals of porphyrin ring has been derived from interpretation of the changes in the Mössbauer spectra of cytochromes before and after redox reactions [19][20][21] To reduce computational complexity of the quantum mechanical calculations, some simplifications have been used. For this reason, the present investigation has been extended to similar complexes of all first-row transition metals.…”
Section: Introductionmentioning
confidence: 99%